2019
DOI: 10.1249/mss.0000000000002175
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-measured Physical Activity, Reproductive Hormones, and DNA Methylation

Abstract: Introduction/Purpose Limited studies have examined the association of physical activity with reproductive hormones, DNA methylation, and pubertal status among adolescents. Methods Among 248 boys and 271 girls, we estimated daily physical activity levels based on 7 d of wrist-worn accelerometer data. We used an isotemporal substitution paradigm and sex-stratified regression models to examine the association of physical activity levels with 1) testosteron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Figure 1 illustrates the PRISMA 2020 flow diagram for the selection process of the studies: a total of 1,473 articles were included from the three databases, and after removing the duplicates and non-eligible studies, 15 articles remained eligible for this review (6 cross-sectional articles, 5 studies reported the acute effects of physical activity, and 5 articles showed the chronic effects of physical activity). The sample size ranged from 12 to 369 participants (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). The age of participants ranged from 9 to 18 years old (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 illustrates the PRISMA 2020 flow diagram for the selection process of the studies: a total of 1,473 articles were included from the three databases, and after removing the duplicates and non-eligible studies, 15 articles remained eligible for this review (6 cross-sectional articles, 5 studies reported the acute effects of physical activity, and 5 articles showed the chronic effects of physical activity). The sample size ranged from 12 to 369 participants (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). The age of participants ranged from 9 to 18 years old (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 12 to 369 participants (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). The age of participants ranged from 9 to 18 years old (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Thirteen studies used blood samples (27,(29)(30)(31)(32)(34)(35)(36)(37)(38)(39)(40) while 2 saliva (33) and buccal swabs (28) respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TEI was calculated using food composition tables 26 . PA was estimated from accelerometers worn for 7 days 27 using Chandler's vector magnitude cutoffs, 28 classified as average sedentary and moderate/vigorous (min/day). Household SES was reported using the Mexican Association of Marketing Research and Public Opinion Agencies questionnaire, consisting of seven categories ranging from A/B (highest SES) to E (lowest SES) 29,30 .…”
Section: Methodsmentioning
confidence: 99%
“…BMI Z scores (BMIz) were calculated based on the World Health Organization reference [ 25 ]. Physical activity information was obtained from the actigraphs (described in detail here [ 26 ]) using Chandler’s vector magnitude cutoffs [ 27 ] and classified as moderate/vigorous hours/day. Total screen time was assessed with a questionnaire adapted for and validated in Mexican adolescents [ 28 ], and was divided into quartiles.…”
Section: Methodsmentioning
confidence: 99%